Studying the problem of determining the coordinate of high-resolution marine targets - Vo, Xung Ha; Nguyễn Trung Kiên; Nguyễn Phùng Bảo; Vũ Quân (Journal of Military Science and Technology, 2022)
For large marine targets, their high-resolution radar images are distributed over many range and azimuth plots. This brings a requirement to estimate the coordinates of the centers of the targets to provide input for tracking filters. The article proposes a method to determine the threshold for binaryization of radar images on the basis of generalization of “the algorithm to determine the optimal threshold for detecting binary quantum signal beams” and estimating large marine target center coordinates.